Ethnomedicinal uses, phytochemistry and bioactivities of Sophora flavescens Ait.: A review - ZHAO Jiaqi; LIU Hong; QIN Rui; HO-YOUNG Choi; YANG Xinzhou (KeAi Communications Co., Ltd., 2021)
Sophora flavescens Ait. also known as Kushen, has been used in China, Japan, Mongolia, India and Korea for thousands of years as a highly traditional herbal medicine. The major phytoconstituents of S. flavescens are flavonoids and alkaloids, which showed a wide range of bioactivities, such as antineoplastic, antiviral, antiinflammatory, antibacterial, and so on. In order to explore active ingredients with medicinal value from S. flavescens and develop Chinese herbal plant resources, we systematically summarized the ethnomedicinal uses, phytochemistry, bioactivities, toxicology and quality control of S. flavescens. Meanwhile, we hope the review will enrich traditional uses and provide reference for pharmacodynamic research, quality evaluation and new drug development.